Islamist terrorism as parochial altruism - Reeve, Zoey (Terrorism and political violence, 2020)
An evolutionary approach is used to explain how certain universal cognitive mechanisms (parochial altruism) underlie engagement and involvement in Islamist terrorism. Parochial altruism is the tendency to perceive and behave in ways that favour ingroups and disfavour outgroups in light of particular intergroup cues, whilst incurring some kind of personal cost to effect that bias. The parochial altruism mechanism influences how ingroups and outgroups are perceived (i.e., as threatened or threatening) and responded to. Experience of certain situations and/or dispositions (i.e., priming contexts of disease, and harm to the ingroup) make parochial altruistic responses more likely. It is argued that Islamist terrorist grievances can be considered as perceptions of evolutionarily relevant threats, whilst terrorism itself is an example of parochial altruistic behaviour. It is further proposed that features associated with engagement in terrorism (including exposure to ideology, propaganda, socialisation, etc.) enhance and guide parochial altruism, that is, perceptions of intergroup threat, and violent responses to it.